A fluorine-free flame-retardant PC / ABS recycled material and preparation method thereof

By using a combination of fluorine-free flame retardant and a modified recovery material in PC/ABS recycled material, combined with reinforcement resin and compatibilizer, a uniform interwoven system is formed, which solves the problems of flame retardancy, mechanical strength, fatigue resistance and wave transmissibility in the prior art, and achieves efficient flame retardant effects and excellent performance.

CN118931145BActive Publication Date: 2025-04-04DONGGUAN GUOHENG PLASTIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411175205.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-04-04
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

In the high-demand communication equipment, existing flame retardant PC/ABS recycling materials are difficult to take into account flame retardant, mechanical strength, fatigue resistance and wave transmissibility.

Method used

Fluorine-free flame retardant combinations include organic phosphorus-based flame retardant and phosphazene-based flame retardant. Combined with modified PC/ABS recovery material, reinforcement resin and compatibility agent, a uniform interwoven system is formed to achieve uniform dispersion of the flame retardant.

Benefits of technology

While maintaining a small amount of flame retardant, the flame retardancy, mechanical strength, fatigue resistance and wave transmissibility of PC/ABS recycled materials are improved, and are suitable for high-demand communication equipment such as 5G antenna shells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005010535420000021
    Figure BDA0005010535420000021
  • Figure BDA0005010535420000071
    Figure BDA0005010535420000071
  • Figure BDA0005010535420000081
    Figure BDA0005010535420000081
Patent Text Reader

Abstract

The present application relates to the field of recycled plastic materials, and discloses a fluorine-free flame-retardant PC / ABS recycled material and a preparation method thereof. The fluorine-free flame-retardant PC / ABS recycled material is made of the following raw materials in percentage by weight: 50-85% of modified PC / ABS recycled material, 2.5-25% of reinforcing resin, 3-15% of compatibilizer, 4-9% of flame retardant, 0.2-4% of lubricant, and 0.3-2% of antioxidant; the flame retardant is composed of an organic phosphorus flame retardant and a phosphazene flame retardant; the modified PC / ABS recycled material is made of PC recycled material, ABS recycled material, styrene-epoxy copolymer, pentaerythritol triallyl ether, silane coupling agent and rosin glycerol ester; preparation method: raw material mixing, melt extrusion, cooling and granulation. The PC / ABS recycled material prepared in this application has good flame retardancy, wave permeability, impact resistance and fatigue resistance, and is used in high-demand communication equipment such as 5G antenna housings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of recycled plastic materials, and more specifically, to a fluorine-free flame-retardant PC / ABS recycled material and a preparation method thereof. Background Art

[0002] PC / ABS material combines the impact resistance, high mechanical strength and molding stability of ABS material, the high strength, temperature resistance and aging resistance of PC material, etc. It is a widely used plastic material that can be used in electronic components, electronic product housings, household appliances, sports equipment, automotive interior and exterior decoration and other industries. PC / ABS materials will generate a large amount of waste materials during the production and consumption process. If these waste materials are directly discarded or landfilled, it will cause serious pollution to the environment. In order to improve the utilization efficiency of waste materials, more and more companies will recycle and reuse these waste materials to reduce production costs, save energy and reduce carbon emissions. The recycled waste materials are usually called PC / ABS recycled materials.

[0003] During the use and multiple processing of PC / ABS recycled materials, the molecular chain may be damaged, resulting in a decrease in the physical properties of PC / ABS recycled materials such as tensile strength, flexural strength, and aging resistance; PC / ABS recycled materials contain a large amount of impurities, such as compatibilizers, toughening resins, fillers, etc., which will also reduce the use performance of PC / ABS recycled materials; the above problems increase the difficulty of processing PC / ABS recycled materials and reduce the application performance of PC / ABS recycled materials; in order to improve the mechanical properties of PC / ABS recycled materials in the prior art, the PC / ABS recycled materials are modified by continuing to add additives such as fillers, toughening resins and compatibilizers to the PC / ABS recycled materials. The additives improve the mechanical properties of PC / ABS recycled materials to a certain extent, which can meet the application of PC / ABS recycled materials in general applications, such as home electronic product shells, automotive interior and exterior decoration, etc.

[0004] However, when the above PC / ABS recycled materials are used in high-demand communication equipment such as 5G antenna shells, they need not only to have good mechanical properties and aging resistance, but also good flame retardant properties and electromagnetic wave penetration characteristics to meet the use requirements. In order to improve the flame retardancy of PC / ABS recycled materials, flame retardant fillers need to be added. Traditional flame retardant fillers are generally fluorine-containing or other halogen-containing flame retardant powders. Generally, a very small amount of addition can achieve a good flame retardant effect, but this type of flame retardant is less environmentally friendly; there are also some relatively environmentally friendly flame retardants, such as antimony trioxide, magnesium hydroxide, aluminum hydroxide, etc., which need to be added in a large amount to achieve a good flame retardant effect. However, the addition of a large amount of flame retardants will not only reduce the performance of the 5G antenna shell in withstanding external mechanical forces such as wind pressure, vibration, and impact, but also reduce the fatigue resistance of the 5G antenna shell in long-term use; in addition, the addition of a large amount of flame retardants will also affect the electromagnetic wave penetration performance of the 5G antenna shell, reducing the signal transmission stability of 5G communication equipment; therefore, the application performance of PC / ABS recycled materials in high-demand communication equipment such as 5G antenna shells is reduced. Summary of the invention

[0005] In order to solve the problem that the existing flame-retardant PC / ABS recycled materials cannot take into account the flame retardancy, mechanical strength, fatigue resistance and wave transmittance when used in high-requirement communication equipment such as 5G antenna housings, the present application provides a fluorine-free flame-retardant PC / ABS recycled material and a preparation method thereof.

[0006] In the first aspect, the present application provides a fluorine-free flame-retardant PC / ABS recycled material, which adopts the following technical scheme: a fluorine-free flame-retardant PC / ABS recycled material, which is prepared from the following raw materials in weight percentage:

[0007]

[0008] The flame retardant is composed of an organic phosphorus flame retardant and a phosphazene flame retardant;

[0009] The modified PC / ABS recycled material is prepared from PC recycled material, ABS recycled material, styrene-epoxy group copolymer, pentaerythritol triallyl ether, silane coupling agent and rosin glycerol ester.

[0010] By adopting the above technical scheme, the fluorine-free flame-retardant PC / ABS recycled material of the present application uses modified PC / ABS recycled material as the material matrix and reinforcing resin as the performance reinforcing material. Under the action of the compatibilizer, the molecular chain segments are evenly interwoven and dispersed to form a dense interwoven system, so that the flame retardant is evenly dispersed in the interwoven system. The PC / ABS recycled material prepared in this way has good flame retardancy as well as good mechanical strength, fatigue resistance and wave transmission.

[0011] Organic phosphorus flame retardants and phosphazene flame retardants are used as flame retardants. In the flame retardant process, free radicals are captured to terminate the combustion chain reaction, and non-flammable gases such as carbon dioxide, ammonia, and nitrogen are decomposed to reduce the concentration of combustible gases and the spread rate of combustible gases. At the same time, phosphoric acid, polyphosphoric acid, metaphosphoric acid and other phosphoric acid compounds produced during combustion promote the dehydration of the polymer to form a carbon layer. Under the synergistic effect of modified PC / ABS recycled materials, excellent flame retardant effects are achieved with a low addition amount of flame retardants. The obtained PC / ABS recycled materials have good flame retardancy and good wave transmittance.

[0012] The modified PC / ABS recycled material is made of PC recycled material, ABS recycled material, styrene-epoxy copolymer, pentaerythritol triallyl ether, silane coupling agent and rosin glycerol ester. Since some molecular segments in PC recycled material and ABS recycled material are broken and contain impurities, the mechanical properties and fatigue resistance of PC recycled material and ABS recycled material are reduced, and the agglomeration of impurities will affect the electromagnetic wave transmittance of the recycled material; the molecular segment of styrene-epoxy copolymer has flexible epoxy groups, which can improve the dispersion uniformity of PC recycled material and ABS recycled material, the branched ether group and branched vinyl structure of pentaerythritol triallyl ether are compatible with organic systems such as PC recycled material and ABS recycled material, and the hydroxyl segment of pentaerythritol triallyl ether can For dispersion of flame retardant, rosin glycerol ester fully softens and infiltrates PC recycled material and ABS recycled material, and silane coupling agent can further disperse the organic system and flame retardant compatibly; under the synergistic effect of styrene-epoxy copolymer, pentaerythritol triallyl ether, silane coupling agent and rosin glycerol ester, the flame retardant is fully dispersed into the interwoven system, while the molecular segments of PC recycled material and ABS recycled material are interwoven with each other, reducing the agglomeration or uneven dispersion of impurity components, and the mechanical strength and fatigue resistance of the modified PC / ABS recycled material are good. The PC / ABS recycled material obtained in this way has good flame retardancy, as well as good mechanical strength, fatigue resistance and wave transmission, and is used in high-requirement communication equipment such as 5G antenna housings.

[0013] Preferably, the organophosphorus flame retardant is hydroquinone bis(diphenyl phosphate) and tetraphenyl bisphenol A diphosphate, the phosphazene flame retardant is polydiphenyloxyphosphazene, and the weight ratio of the tetraphenyl bisphenol A diphosphate, the hydroquinone bis(diphenyl phosphate) and the polydiphenyloxyphosphazene is (1-2):(3-8):(1-3).

[0014] By adopting the above technical scheme, polydiphenyloxyphosphazene is used as a phosphazene flame retardant, nitrogen elements and phosphorus elements are alternately arranged on the main chain of the polydiphenyloxyphosphazene, and the side chain is a phenoxy group, which gives it good flame retardancy and flexibility, and it can remain stable at high temperatures and promote the formation of a carbon layer. Hydroquinone bis(diphenyl phosphate) and tetraphenyl bisphenol A diphosphate are used as organic phosphorus flame retardants, and phosphoric acid, polyphosphoric acid, metaphosphoric acid and other phosphoric acid compounds produced during combustion can further promote the formation of a carbon layer; therefore, tetraphenyl bisphenol A diphosphate, hydroquinone bis(diphenyl phosphate) and polydiphenyloxyphosphazene with a better dosage ratio are used as flame retardants, and the three have a good synergistic effect. When added to modified PC / ABS recycled materials, the flame retardancy of the prepared PC / ABS recycled materials can be improved under the synergistic effect of the modified PC / ABS recycled materials, reinforcing resins and compatibilizers, while the prepared PC / ABS recycled materials have good mechanical strength and fatigue resistance, and can maintain good wave transmission.

[0015] Preferably, the modified PC / ABS recycled material is prepared from the following raw materials in parts by weight:

[0016] 60-80 PC recycled materials

[0017] 15-25 parts of ABS recycled materials

[0018] Styrene-epoxy copolymer 15-25 parts

[0019] Pentaerythritol triallyl ether 4-8 parts

[0020] Silane coupling agent 3-6 parts

[0021] 2-5 parts of rosin glycerol ester.

[0022] By adopting the above technical scheme, styrene-epoxy copolymer, pentaerythritol triallyl ether, silane coupling agent and rosin glycerol ester are compounded in an optimal dosage ratio to enhance the synergy of PC recycled materials and ABS recycled materials, so that the prepared modified PC / ABS recycled materials can have good impact resistance as well as good flame retardancy, fatigue resistance and wave transmission.

[0023] Preferably, the silane coupling agent is composed of Si-69 silane coupling agent and γ-glycidyloxypropyltrimethoxysilane in a weight ratio of 1:(0.1-0.3).

[0024] By adopting the above technical scheme, Si-69 silane coupling agent and γ-glycidyloxypropyltrimethoxysilane are compounded in an optimal dosage ratio, which can further improve the mixing uniformity of the flame retardant and the modified PC / ABS recycled material, thereby improving the dispersibility of the flame retardant in the modified PC / ABS recycled material, and improving the mechanical properties, flame retardancy and wave transmission of the prepared PC / ABS recycled material.

[0025] Preferably, the modified PC / ABS recycled material is prepared by the following steps:

[0026] A1. Grind the PC recycled materials and ABS recycled materials separately, and sieve out the PC recycled materials and ABS recycled materials with a particle size of 0.5-5mm;

[0027] A2. Pickling, water washing and drying the screened PC recycled materials and ABS recycled materials respectively;

[0028] A3, adding acid-washed PC recycled material, acid-washed ABS recycled material, styrene-epoxy copolymer, pentaerythritol triallyl ether, silane coupling agent and rosin glycerol ester in proportion, mixing, melt extruding, cooling, pelletizing, and preparing modified PC / ABS recycled material.

[0029] By adopting the above technical scheme, the PC recycled materials and the ABS recycled materials are first crushed and screened respectively. Since the impurity components have low plasticity, they are easily broken into small molecular particles under the shearing and collision during crushing. Therefore, it is necessary to screen out the PC recycled materials and the ABS recycled materials with a particle size less than 0.5 mm and remove them; and the PC recycled materials and the ABS recycled materials with a particle size greater than 5 mm need to be recycled and crushed again to make the particle size meet the required standards; then the PC recycled materials and the ABS recycled materials with a particle size of 0.5-5 mm are respectively pickled to further remove some impurity components in the PC recycled materials and the ABS recycled materials; then the pickled PC recycled materials and the pickled ABS recycled materials are mixed and modified to improve the interweaving and dispersion uniformity between the molecular segments of the PC recycled materials and the ABS recycled materials, and to improve the mechanical strength and fatigue resistance of the prepared modified PC / ABS recycled materials.

[0030] Preferably, the reinforcing resin is composed of silicone PC resin and SEBS in a weight ratio of 1:(0.2-0.4).

[0031] By adopting the above technical solution, polydimethylsiloxane chain segments are introduced into the silicone PC resin, which increases the length and electrical stability of the flexible structural unit, reduces the rigidity of the benzene ring, and can be interwoven and dispersed with the SEBS molecular chain segments. The two produce a good synergistic effect, further improving the mechanical strength and fatigue resistance of PC / ABS recycled materials, while improving the dispersion uniformity of the flame retardant in the system, and improving the flame retardancy and wave transmission of PC / ABS recycled materials.

[0032] Preferably, the compatibilizer is composed of glycidyl methacrylate-styrene-acrylonitrile copolymer and styrene-acrylate copolymer in a weight ratio of 1:(1-3).

[0033] By adopting the above technical scheme, the glycidyl methacrylate-styrene-acrylonitrile copolymer and the styrene-acrylate copolymer with an optimal dosage ratio work together to improve the dispersion uniformity of modified PC / ABS recycled materials, reinforcing resins, flame retardants and other components, thereby improving the mechanical strength, fatigue resistance, flame retardancy and wave transmission of the prepared PC / ABS recycled materials.

[0034] Preferably, the lubricant is any one or a combination of polydimethylsiloxane, silicone powder, paraffin, polyethylene wax, calcium stearate, zinc stearate, stearic acid amide and N,N-ethylene bisstearic acid amide.

[0035] By adopting the above technical solution, the above lubricant can better improve the processing fluidity and viscosity of PC / ABS recycled materials, reduce the friction of each component during extrusion molding, and improve processing stability.

[0036] Preferably, the antioxidant is antioxidant 1010 and / or antioxidant 168.

[0037] By adopting the above technical solution, the above oxidant can better improve the aging resistance of the prepared PC / ABS recycled material.

[0038] In the second aspect, the present application provides a method for preparing fluorine-free flame-retardant PC / ABS recycled materials, using the following technical solution:

[0039] A method for preparing fluorine-free flame-retardant PC / ABS recycled material comprises the following steps: uniformly mixing modified PC / ABS recycled material, reinforcing resin, compatibilizer, flame retardant, lubricant and antioxidant, melt-extruding, cooling and pelletizing to obtain fluorine-free flame-retardant PC / ABS recycled material.

[0040] By adopting the above technical scheme, the above raw materials are mixed and melt-extruded, cooled, and pelletized to obtain fluorine-free flame-retardant PC / ABS recycled materials with stable performance.

[0041] In summary, this application has the following beneficial effects:

[0042] 1. The fluorine-free flame-retardant PC / ABS recycled material of the present application uses modified PC / ABS recycled material made of PC recycled material, ABS recycled material, styrene-epoxy group copolymer, pentaerythritol triallyl ether, silane coupling agent and rosin glycerol ester as the material matrix, and reinforcing resin as the performance reinforcing material. Under the action of the compatibilizer, the molecular chain segments are evenly dispersed to form a dense interwoven system, so that the flame retardant composed of organic phosphorus flame retardant and phosphazene flame retardant is evenly dispersed in the interwoven system. The PC / ABS recycled material prepared in this way has good flame retardancy, as well as good mechanical strength, fatigue resistance and wave transmission, and is used in high-requirement communication equipment such as 5G antenna housings.

[0043] 2. Using tetraphenyl bisphenol A diphosphate and hydroquinone bis(diphenyl phosphate) in a better dosage ratio as organic phosphorus flame retardants and polydiphenyloxyphosphazene as phosphazene flame retardant, the three produce a good synergistic effect. Under the joint action of modified PC / ABS recycled materials, reinforcing resins and compatibilizers, excellent flame retardant effects can be achieved at a smaller dosage. The obtained PC / ABS recycled materials have good mechanical strength and fatigue resistance, and can maintain good wave transmission.

[0044] 3. This application uses silicone PC resin and SEBS in an optimal dosage ratio as reinforcing resins, and uses glycidyl methacrylate-styrene-acrylonitrile copolymer and styrene-acrylate copolymer in an optimal dosage ratio as compatibilizers, which can be well compounded with modified PC / ABS recycled materials to improve the mechanical strength and fatigue resistance of the prepared PC / ABS recycled materials, while improving the flame retardancy and wave transmission of the PC / ABS recycled materials. DETAILED DESCRIPTION

[0045] The present application is further described in detail below in conjunction with embodiments.

[0046] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used:

[0047] 1. PC recycled material: commercially available, cantilever beam notch impact strength: 15-18kg-cm / cm, heat deformation temperature 75-78℃, bending strength 23-28MPa, dielectric constant 3.5-3.6, household appliance shell plastic waste recycling by Heilongjiang Zhongrecycling Waste Appliance Dismantling Co., Ltd.;

[0048] 2. ABS recycled material: commercially available, cantilever beam notched impact strength: 20-23kg-cm / cm, heat deformation temperature 80-85°C, bending strength 15-18MPa, dielectric constant 3.6-3.7, household appliance shell plastic waste recycling by Heilongjiang Zhongzao Waste Appliance Dismantling Co., Ltd.;

[0049] 3. Hydroquinone bis(diphenyl phosphate): CAS No. 51732-57-1, content 99.8%;

[0050] 4. Tetraphenyl bisphenol A diphosphate: CAS No. 181028-79-5, content 99%;

[0051] 5. Polydiphenyloxyphosphazene: CAS No. 28212-48-8, content 98%;

[0052] 6. Styrene-epoxy copolymer: KS-05, density 1.02-1.08g / cm 3 , melting rate 22-28g / 10min, epoxy group content 2-4%;

[0053] 7. Pentaerythritol triallyl ether: CAS No. 1471-17-6, content 99%;

[0054] 8. Rosin glycerol ester: CAS number: 8050-30-4, content 99%;

[0055] 9. Silicone PC resin: Wanhua Chemical STC3711;

[0056] 10. SEBS: Kraton G1726;

[0057] 11. Glycidyl methacrylate-styrene-acrylonitrile copolymer: Jiayirong, SBG-001;

[0058] 12. Styrene-acrylate copolymer: Jiayirong HPC-3128;

[0059] 13. Polydimethylsiloxane: Dow Corning PMX561;

[0060] 14. Polyethylene wax: Honeywell, AC-629A;

[0061] 15. Styrene grafted maleic anhydride: maleic anhydride content 17-18%.

[0062] Preparation example of modified PC / ABS recycled material

[0063] Preparation Example 1

[0064] Preparation Example 1 discloses a modified PC / ABS recycled material, which is prepared by the following steps:

[0065] A1. Use a pulverizer to crush PC recycled materials and ABS recycled materials respectively, control the crushing rate to 800r / min, crush for 40min, and screen after crushing, remove PC recycled materials and ABS recycled materials with a particle size of less than 0.5mm, and screen out PC recycled materials and ABS recycled materials with a particle size of 0.5-5mm; PC recycled materials and ABS recycled materials with a particle size greater than 5mm need to be crushed and screened again after being screened out to meet the particle size requirements;

[0066] A2. Use pickling agent to pickle the PC recycled materials and ABS recycled materials with particle sizes of 0.5-5 mm respectively, control the pickling temperature to 20°C, the pickling time to 30 minutes, wash with water and dry at 70°C;

[0067] A3, 6 kg of acid-washed PC recycled material, 2.5 kg of acid-washed ABS recycled material, 1.5 kg of styrene-epoxy group copolymer, 0.8 kg of pentaerythritol triallyl ether, 0.6 kg of vinyl trimethoxysilane as a silane coupling agent and 0.2 kg of rosin glycerol ester were mixed, melt-extruded at a temperature of 210° C. using a twin-screw extruder, water-cooled, and pelletized to obtain modified PC / ABS recycled material;

[0068] The pickling agent in step A2 is a commercially available pickling agent, which consists of 2 wt % hydrochloric acid, 1 wt % hydroxyethyl cellulose, 2 wt % TO-8 and 95 % water.

[0069] Preparation Example 2-4

[0070] The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.

[0071] Table 1 Raw material dosage and preparation conditions of Preparation Examples 1-3

[0072]

[0073]

[0074] Preparation Example 4

[0075] The difference between Preparation Example 4 and Preparation Example 1 is that the silane coupling agent is different. The silane coupling agent in Preparation Example 4 consists of Si-69 silane coupling agent and γ-glycidyloxypropyltrimethoxysilane. The amount of Si-69 silane coupling agent is 0.55 kg, and the amount of γ-glycidyloxypropyltrimethoxysilane is 0.05 kg. The rest is the same as Preparation Example 1.

[0076] Preparation Example 5

[0077] The difference between Preparation Example 5 and Preparation Example 4 is that the amount of Si-69 silane coupling agent used is 0.46 kg, the amount of γ-glycidyloxypropyltrimethoxysilane used is 0.14 kg, and the rest is the same as Preparation Example 4.

[0078] Preparation Comparative Example 1

[0079] The difference between Preparation Comparative Example 1 and Preparation Example 1 is that the styrene-epoxy copolymer is replaced by an equal amount of styrene-maleic anhydride copolymer, model SMA1000, and the rest is the same as Preparation Example 1.

[0080] Preparation Comparative Example 2

[0081] The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of pentaerythritol triallyl ether is replaced by polyethylene glycol diglycidyl ether, and the rest is the same as Preparation Example 1.

[0082] Preparation Comparative Example 3

[0083] The difference between Preparation Comparative Example 3 and Preparation Example 1 is that an equal amount of rosin glycerol ester is replaced by pentaerythritol triallyl ether, and the rest is the same as Preparation Example 1.

[0084] Example

[0085] Example 1

[0086] Example 1 discloses a fluorine-free flame-retardant PC / ABS recycled material, which is prepared by the following steps: taking 5 kg of the modified PC / ABS recycled material prepared in Preparation Example 1, 2.5 kg of silicone PC resin as a reinforcing resin, 1.5 kg of glycidyl methacrylate-styrene-acrylonitrile copolymer as a compatibilizer, 0.4 kg of flame retardant (composed of triphenyl phosphate and hexaphenoxy cyclotriphosphazene in a weight ratio of 1:1), 0.4 kg of polydimethylsiloxane as a lubricant and 0.2 kg of antioxidant The agent (composed of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1) was evenly mixed, and a twin-screw extruder was used. Under the condition of a screw speed of 200r / min, the extrusion temperature of zone one was controlled to be 220°C, the extrusion temperature of zone two was controlled to be 225°C, the extrusion temperature of zone three was controlled to be 230°C, the extrusion temperature of zone four was controlled to be 245°C, the extrusion temperature of zone five was controlled to be 240°C, and the extrusion temperature of die head was controlled to be 235°C. The materials were melt-extruded, water-cooled, and pelletized to obtain fluorine-free flame-retardant PC / ABS recycled materials.

[0087] Example 2-3

[0088] The difference between Example 2-3 and Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 2 below for details.

[0089] Table 2 Raw material dosage and preparation conditions of Examples 1-3

[0090]

[0091]

[0092] Embodiment 4-5

[0093] The difference between Example 4-5 and Example 1 is that the sources of the modified PC / ABS recycled materials are different, see Table 3 below for details.

[0094] Table 3 Sources of modified PC / ABS recycled materials of Examples 4-5

[0095] Example Sources of Modified PC / ABS Recycled Materials Example 4 Preparation Example 4 Example 5 Preparation Example 5

[0096] Example 6

[0097] The difference between Example 6 and Example 5 is that the flame retardant is different. The flame retardant in Example 6 is composed of tetraphenyl bisphenol A diphosphate, hydroquinone bis(diphenyl phosphate) and polydiphenyloxyphosphazene. The amount of tetraphenyl bisphenol A diphosphate is 0.1 kg, the amount of hydroquinone bis(diphenyl phosphate) is 0.15 kg, and the amount of polydiphenyloxyphosphazene is 0.15 kg. The rest is the same as Example 5.

[0098] Example 7

[0099] The difference between Example 7 and Example 6 is that the amount of tetraphenyl bisphenol A diphosphate is 0.04 kg, the amount of hydroquinone bis(diphenyl phosphate) is 0.32 kg, the amount of polydiphenyloxyphosphazene is 0.04 kg, and the rest is the same as Example 6.

[0100] Example 8

[0101] The difference between Example 8 and Example 7 is that the reinforcing resin is different. The reinforcing resin in Example 8 is composed of silicone PC resin and SEBS. The amount of silicone PC resin is 2.08 kg, and the amount of SEBS is 0.42 kg. The rest is the same as Example 7.

[0102] Example 9

[0103] The difference between Example 9 and Example 8 is that the amount of silicone PC resin used is 1.786 kg, the amount of SEBS used is 0.714 kg, and the rest is the same as Example 8.

[0104] Example 10

[0105] The difference between Example 10 and Example 8 is that the compatibilizer is different. The compatibilizer in Example 10 is composed of glycidyl methacrylate-styrene-acrylonitrile copolymer and styrene-acrylate copolymer. The amount of glycidyl methacrylate-styrene-acrylonitrile copolymer is 0.75 kg, and the amount of styrene-acrylate copolymer is 0.75 kg. The rest is the same as Example 8.

[0106] Embodiment 11

[0107] The difference between Example 11 and Example 10 is that the amount of glycidyl methacrylate-styrene-acrylonitrile copolymer used is 0.375 kg, the amount of styrene-acrylate copolymer used is 1.125 kg, and the rest is the same as Example 10.

[0108] Comparative Example

[0109] Comparative Examples 1-3

[0110] The difference between Comparative Examples 1-3 and Example 1 is that the sources of the modified PC / ABS recycled materials are different, see Table 4 below for details.

[0111] Table 4 Sources of modified PC / ABS recycled materials of Comparative Examples 1-3

[0112] Comparative Example Sources of Modified PC / ABS Recycled Materials Comparative Example 1 Preparation Comparative Example 1 Comparative Example 2 Preparation Comparative Example 2 Comparative Example 3 Preparation Comparative Example 3

[0113] Comparative Example 4

[0114] The difference between Comparative Example 4 and Example 1 is that the flame retardant consists of magnesium hydroxide and a phosphazene flame retardant, the phosphazene flame retardant is phenoxycyclotriphosphazene, the amount of magnesium hydroxide used is 0.3 kg, the amount of phenoxycyclotriphosphazene used is 0.1 kg, and the rest is the same as Example 1.

[0115] Comparative Example 5

[0116] The difference between Comparative Example 5 and Example 1 is that the flame retardant is composed of an organosilicon flame retardant, an organophosphorus flame retardant and a phosphazene flame retardant, the organosilicon flame retardant is polymethylphenylsiloxane, the organophosphorus flame retardant is hydroquinone bis(diphenyl phosphate), the phosphazene flame retardant is polydiphenyloxyphosphazene, the amount of polymethylphenylsiloxane is 0.2kg, the molecular weight of polymethylphenylsiloxane is 2500-2700, the amount of hydroquinone bis(diphenyl phosphate) is 0.1kg, the amount of polydiphenyloxyphosphazene is 0.1kg, and the rest is the same as Example 1.

[0117] Performance testing

[0118] The following is a performance test of the fluorine-free flame-retardant PC / ABS recycled materials prepared in Examples 1-11 and Comparative Examples 1-5. The PC / ABS recycled materials prepared above were placed in an oven at 80°C for 90 minutes, and injection molded at 240°C using an injection molding tester, and cut into test strips for testing:

[0119] 1. Impact strength test

[0120] According to the test standard of ASTM D256, the test strip is subjected to the Izod notched impact strength test (unit: kg-cm / cm), recorded as the first impact strength, and the test results are tested and recorded;

[0121] 2. Fatigue resistance test

[0122] The test strip was placed in an ultrasonic wave, the water temperature was controlled to be 85°C, the ultrasonic frequency was 30kHz, and the vibration test was performed for 8 hours. Then, the test strip was placed in a constant temperature and humidity chamber at a temperature of 85°C and a humidity of 85% for 8 hours. After the test was completed, the test strip was subjected to a cantilever beam notched impact strength test (unit: kg-cm / cm) according to the test standard of ASTM D256, which was recorded as the second impact strength. The test results were tested and recorded.

[0123] 3. Bending strength test

[0124] According to the test standard of ASTM D790, the bending strength of the test strip is tested (unit: MPa), and the test results are recorded;

[0125] 4. Flame retardancy test

[0126] According to the UL94 vertical burning test standard, the flame retardancy test was conducted on the test strip with a thickness of 0.8 mm, and the test results were recorded;

[0127] 5. Dielectric constant test

[0128] Use a dielectric constant tester, model: ZJD-C, to test the dielectric constant of the test strip (1KHz), test and record the test results;

[0129] The following are the performance test data of the fluorine-free flame-retardant PC / ABS recycled materials prepared in Examples 1-11 and Comparative Examples 1-5, see Table 5 below for details.

[0130] Table 5 Performance data of Examples 1-12 and Comparative Examples 1-5

[0131]

[0132]

[0133] From the above data, it can be seen that compared with Example 1, the first impact strength of the PC / ABS recycled material obtained in Example 4-5 is increased by 1.5kg-cm / cm, the second impact strength after fatigue resistance test is increased by 3kg-cm / cm, and the bending strength is slightly increased, indicating that the use of Si-69 silane coupling agent and γ-glycidyloxypropyl trimethoxysilane in the preferred dosage ratio of the present application as a silane coupling agent, and compounding with the styrene-epoxy copolymer, pentaerythritol triallyl ether and rosin glycerol ester of the present application can better improve the impact resistance and fatigue resistance of the obtained PC / ABS recycled material, and the dielectric constant is reduced by 0.07. The low dielectric constant indicates that the polarization degree of PC / ABS recycled material in the electric field is low, so the movement of carriers and energy consumption in the dielectric will also be reduced accordingly, thereby making the dielectric loss of PC / ABS recycled material better, and therefore also has better wave transmittance.

[0134] Compared with Example 1, the first impact strength of the PC / ABS recycled material obtained in Comparative Examples 1-3 is reduced by 7.2 kg-cm / cm, the second impact strength after fatigue resistance test is reduced by 15.5 kg-cm / cm, the bending strength is reduced by 11.4 MPa, the flame retardant grade is also reduced from VO to VI, and the dielectric constant is increased by 0.65. This may be because the styrene-epoxy copolymer, pentaerythritol triallyl ether, silane coupling agent and rosin glycerol ester are not compounded in a better dosage ratio in Comparative Examples 1-3, and the four have a good synergistic effect, which can evenly interweave and disperse the PC recycled material and the ABS recycled material, improve the obtained PC / ABS recycled material has good impact strength, bending strength and fatigue resistance, while making the impurity components and flame retardants fully dispersed, the molecular chain segments have good rigidity and good flexibility, and therefore have good flame retardancy and wave transmission.

[0135] Compared with Comparative Examples 4-5, Example 4-7 uses the preferred dosage ratio of the organic phosphorus flame retardant and the phosphazene flame retardant of the present application for compounding, which can improve the flame retardant properties of the obtained PC / ABS recycled material, and the flame retardant grade is increased from V2 and V1 to VO, and the impact strength, bending strength, fatigue resistance and wave transmittance of the obtained PC / ABS recycled material are all improved; in Comparative Example 4, magnesium hydroxide flame retardant and phosphazene flame retardant are used as flame retardants, and the mechanical properties of the obtained PC / ABS recycled material are reduced, and the dielectric constant is significantly improved; while in Comparative Example 5, silicone flame retardant, organic phosphorus flame retardant and phosphazene flame retardant are used as flame retardants, and the mechanical properties of the obtained PC / ABS recycled material are reduced, and the dielectric constant is also slightly improved.

[0136] Compared with Example 7, Examples 8-9 use a better dosage ratio of silicone PC resin and SEBS resin for compounding, which can better improve the impact strength, bending strength, fatigue resistance and wave transmission of the prepared PC / ABS recycled materials. This may be because the silicone PC resin and SEBS resin can further improve the dispersion properties of flame retardants and modified PC / ABS recycled materials.

[0137] Compared with Example 8, Examples 10-11 use a reinforcing resin and a compatibilizer composed of glycidyl methacrylate-styrene-acrylonitrile copolymer and styrene-acrylate copolymer for compounding, which can further improve the impact strength and fatigue resistance of the prepared PC / ABS recycled material while improving the wave transmission.

[0138] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fluorine-free flame-retardant PC / ABS recycled material, characterized in that: Made from the following raw materials in weight percentage: Modified PC / ABS recycled material 50-85% Reinforcement resin 5-25% Compatibilizer 3-15% Flame retardant 4-9% Lubricant 0.2-4% Antioxidants 0.3-2%; The flame retardant is composed of an organic phosphorus flame retardant and a phosphazene flame retardant; the organic phosphorus flame retardant is hydroquinone bis(diphenyl phosphate) and tetraphenyl bisphenol A diphosphate, the phosphazene flame retardant is polydiphenyloxyphosphazene, and the weight ratio of the tetraphenyl bisphenol A diphosphate, the hydroquinone bis(diphenyl phosphate) and the polydiphenyloxyphosphazene is (1-2):(3-8):(1-3); The modified PC / ABS recycled material is prepared from the following raw materials in parts by weight: 60-80 PC recycled materials 15-25 parts of ABS recycled materials Styrene-epoxy copolymer 15-25 parts Pentaerythritol triallyl ether 4-8 parts Silane coupling agent 3-6 parts 2-5 parts of rosin glycerol ester; The silane coupling agent is composed of Si-69 silane coupling agent and γ-glycidyloxypropyltrimethoxysilane in a weight ratio of 1:(0.1-0.3); The modified PC / ABS recycled material is prepared by the following steps: A1. Grind the PC recycled materials and ABS recycled materials separately, and sieve out the PC recycled materials and ABS recycled materials with a particle size of 0.5-5mm; A2. Pickling, water washing and drying the screened PC recycled materials and ABS recycled materials respectively; A3, adding the PC recycled material after pickling, the ABS recycled material after pickling, the styrene-epoxy copolymer, the pentaerythritol triallyl ether, the silane coupling agent and the rosin glycerol ester in proportion, mixing, melt-extruding, cooling, and pelletizing to obtain the modified PC / ABS recycled material; The reinforcing resin is composed of silicone PC resin and SEBS in a weight ratio of 1:(0.2-0.4).

2. A fluorine-free flame-retardant PC / ABS recycled material according to claim 1, characterized in that: The compatibilizer is composed of a glycidyl methacrylate-styrene-acrylonitrile copolymer and a styrene-acrylate copolymer in a weight ratio of 1:(1-3).

3. The fluorine-free flame-retardant PC / ABS recycled material according to claim 1, characterized in that: The lubricant is any one or a combination of polydimethylsiloxane, silicone powder, paraffin, polyethylene wax, calcium stearate, zinc stearate, stearic acid amide and N,N-ethylene bis stearic acid amide.

4. The fluorine-free flame-retardant PC / ABS recycled material according to claim 1, characterized in that: The antioxidant is antioxidant 1010 and / or antioxidant 168.

5. A method for preparing a fluorine-free flame-retardant PC / ABS recycled material as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: The modified PC / ABS recycled material, reinforcing resin, compatibilizer, flame retardant, lubricant and antioxidant are uniformly mixed, melt-extruded, cooled and pelletized to obtain fluorine-free flame-retardant PC / ABS recycled material.

Citation Information

Patent Citations

  • High flexible flame retardant PC(polycarbonate) / ABS alloy

    CN101003676A

  • PC / ABS alloy

    CN101173090A